Biocompatibility Assessment of Novel Bioresorbable Alloys Mg-Zn-Se and Mg-Zn-Cu for Endovascular Applications: In- Vitro Studies - Persaud-Sharma, Dharam (2013)
Previous studies have shown that using biodegradable magnesium alloys such as Mg-Zn and Mg-Zn-Al possess the appropriate mechanical properties and biocompatibility to serve in a multitude of biological applications ranging from endovascular to orthopedic and fixation devices. The objective of this study was to evaluate the biocompatibility of novel as-cast magnesium alloys Mg-1Zn-1Cu wt.% and Mg-1Zn-1Se wt.% as potential implantable biomedical materials, and compare their biologically effective properties to a binary Mg-Zn alloy. The cytotoxicity of these experimental alloys was evaluated using a tetrazolium based- MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assay and a lactate dehydrogenase membrane integrity assay (LDH). The MTS assay was performed on extract solutions obtained from a 30-day period of alloy immersion and agitation in simulated body fluid to evaluate the major degradation products eluted from the alloy materials. Human foreskin fibroblast cell growth on the experimental magnesium alloys was evaluated for a 72 hour period, and cell death was quantified by measuring lactate dehydrogenase concentrations. Both Mg-Zn-Se and Mg-Zn-Cu alloys exhibit low cytotoxicity levels which are suitable for biomaterial applications. The Mg-Zn-Cu alloy was found to completely degrade within 72 hours, resulting in lower human foreskin fibroblast cell viability. The Mg-Zn-Se alloy was shown to be less cytotoxic than both the Mg-Zn-Cu and Mg-Zn alloys.